Om noen praktiske spørsmål i tospråklig leksikografi - Haraldsson, Helgi (Nordiske Studier i Leksikografi, 2007)
The article discusses the relation between conventional textbooks of grammar, dictionary grammars and grammatical information in the lemma list section (the dictionary proper) in a bilingual dictionary. The treatment of synonym groups is also commented upon. Particular attention is given to grammatical categories that exist only in one of the two languages involved, such as the definite article in Nordic languages versus Russian and other Slavic languages, the aspect category in the latter which is absent in Nordic languages. It is important that these differences are clarified and explained as meticulously as possible by concrete indications and examples of use. Instances of this are shown, e.g the problem of translating examples containing the only Russian past tense into Germanic languages which possess a number of past tenses, e.g. the choice between ”aoristic” and ”perfectivic” meaning of the Russian perfective past tense. Furthermore it is of paramount importance not to overlook differences in the meaning structure and extension (range of meanings) of the source language lemma and its primary equivalent in the target language. A comparison of the solution of such problems in three different dictionaries is presented. The use of a certain category, existing in both source and target language, may reveal subtle differences not to be ignored. An instance of this is a specific use of the grammaticalized definite article in Norwegian and Icelandic, an idiosyncrasy that is not heeded in textbooks. Needless to say, it is practically impossible to cover all the above-mentioned differences by examples in every concrete case, and ad hoc solution must be applied to a great extent.